2008
DOI: 10.1007/s11239-008-0298-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of practice pattern for venous thromboembolism prevention in Lebanese hospitals

Abstract: This study reflected the importance of assessing VTE prophylaxis in Lebanese hospitals, thus, the need for implementing established guidelines to improve the overall patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
4
14
3
Order By: Relevance
“…Zeitoun et al, concluded that the need for implementing proved guidelines was needed to improve the overall patient safety. They recorded that inappropriate VTE prophylaxis was administered in 35% of the subjects in lowrisk group, 70% of the subjects in the moderate-risk group, and 39% of the subjects in the high-risk group (P < 0.0001) (11). In the current study the prophylaxis was inadequate in 83.33% of moderate and 65.79% of high risk group subjects.…”
Section: Discussionmentioning
confidence: 44%
“…Zeitoun et al, concluded that the need for implementing proved guidelines was needed to improve the overall patient safety. They recorded that inappropriate VTE prophylaxis was administered in 35% of the subjects in lowrisk group, 70% of the subjects in the moderate-risk group, and 39% of the subjects in the high-risk group (P < 0.0001) (11). In the current study the prophylaxis was inadequate in 83.33% of moderate and 65.79% of high risk group subjects.…”
Section: Discussionmentioning
confidence: 44%
“…19,20,21,22 A similar study done at a Lebanese hospital has shown appropriateness of VTE prophylaxis in 51.2 % to 67.2 % of the patients. 23 In the present study out of the 69% of the high risk medical patient population only 30.4% received effective thromboprophylaxis for VTE and 4.33% of the high-risk patients received ineffective thromboprophylaxis and 65.21% of the high risk medical patient population did not receive any effective thromboprophylaxis. Among the low risk population only 3% received effective thromboprophylaxis.…”
Section: Malecontrasting
confidence: 45%
“…Zeitoun et al [21] concluded that patients with moderate risk of VTE were more likely to receive inappropriate prophylaxis than patients with low and high risk of VTE. Deheinzelin et al [17] found that with high risk and moderate risk patients were more likely to receive inappropriate prophylaxis than patients with low risk of VTE.…”
Section: Thromboembolic Events Prophylaxis J Hematol 2015;4(4):223-227mentioning
confidence: 99%